2013
DOI: 10.1186/1472-6963-13-255
|View full text |Cite
|
Sign up to set email alerts
|

Local co-ordination and case management can enhance Indigenous eye care – a qualitative study

Abstract: BackgroundIndigenous adults suffer six times more blindness than other Australians but 94% of this vision loss is unnecessary being preventable or treatable. We have explored the barriers and solutions to improve Indigenous eye health and proposed significant system changes required to close the gap for Indigenous eye health. This paper aims to identify the local co-ordination and case management requirements necessary to improve eye care for Indigenous Australians.MethodsA qualitative study, using semi-struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…In the Katherine region, key barriers to eye care include complex sociocultural determinants, unclear eye care referral processes, lengthy ophthalmology waiting lists and challenges coordinating patient eye care between various providers, including ACCHSs, hospitals and non‐government organisations . These factors contribute to suboptimal eye care service delivery, resulting in sustained poor eye health outcomes for Aboriginal and Torres Strait Islander people in the region …”
Section: Problemmentioning
confidence: 99%
“…In the Katherine region, key barriers to eye care include complex sociocultural determinants, unclear eye care referral processes, lengthy ophthalmology waiting lists and challenges coordinating patient eye care between various providers, including ACCHSs, hospitals and non‐government organisations . These factors contribute to suboptimal eye care service delivery, resulting in sustained poor eye health outcomes for Aboriginal and Torres Strait Islander people in the region …”
Section: Problemmentioning
confidence: 99%
“…27,30 Secondary and tertiary eye care coordination included organising and facilitating surgery attendance, booking travel and accommodation for ophthalmic care, and ensuring appropriate follow-up care. 38,41 Key providers of eye care coordination and associated support included eye health coordinators, 11,12,[24][25][26]30,34,35,40,41 Aboriginal Health Workers (AHWs), 23,25,27,34 primary health care staff, 34,38,41 and community liaison staff. 12,23 One study reported that support provided by regional eye health coordinators was intended to cover multiple communities, but in practice was delivered only to the communities where the coordinators resided.…”
Section: Coordination Of Carementioning
confidence: 99%
“…9 A previous study 10 identified the importance of non-clinical support for Indigenous eye care at the community level, particularly given socio-cultural determinants, such as limited understanding of English, poverty, historical trauma, and racism, that make access to services difficult for Indigenous patients. Eye care coordination involves many non-clinical aspects and is critical for ensuring that patients attend care, 11,12 but specific funding for such activities is limited. 13 Given the need for better and more accessible eye care services for Indigenous Australians, it is important to understand what constitutes non-clinical support and to know who provides it.…”
mentioning
confidence: 99%
“…4,14,15 Appointing a dedicated coordinator for teleophthalmology should be considered by state health services. This requires coordination of services between GPs, optometrists and ophthalmologists, based on up-to-date knowledge of service providers, regional facilities, IT and administrative support.…”
Section: Analysis and Interpretationmentioning
confidence: 99%